The Role of Learning Communities in Developing Teacher Competence - Chika Nurcahyani Timur; Suyatno Suyatno; Achadi Budi Santosa (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
This study aims to determine the role of learning communities in developing teacher competencies at SMP Muhammadiyah 1 Balikpapan. The type of research used is qualitative descriptive research with a case study method. Data collection techniques through interviews, observations and document studies. The results of the study indicate that learning communities that are routinely implemented in schools provide positive changes to teacher competencies that have an impact on the learning process of students. Active and enjoyable learning will certainly affect the motivation and activeness of students in participating in learning. Learning communities are also a place for professional and character development for educators to be more active, creative and confident. The findings indicate that active involvement in such communities significantly contributes to improved instructional practices, increased self-efficacy, and stronger professional identity. The study concludes that learning communities serve as a vital component in teacher professional development and recommends institutional support for their sustainability.